Fuentes de sustratos orgánicos en plantas injertadas de cacao (Theobroma cacao L.) bajo condiciones de vivero en el distrito de la Banda de Shilcayo-San Martín - Pinchi Pinchi, Fredy (2008)
The present work investigation was carried of the nursery of the institute of tropical crops, located to 2,5 km. of the city of Tarapoto, Banda of Shilcayo, district County and Department of San Martin; looking for to standardize a source of organic matter to produce grafts implanted with good characteristics for the transplante as soon as posible and smaller cost. To get this had as objectives: To determine the best effect of sources of organic matter in the growth of grafts and implants of cocoa and to determine the economic analysis of the treatments in study. Sources of organic matter were proven (a1 = worm Humus, a2 = decomposed Pulpof coffee, a3 = Gallinaza of insolent posture, a4 = manure of bovine livestock and a0 = agricultural Earth), three clones of cocoa (b1 = CCN 51, b2 = IMC 67 and b3 = ICS 1). The design experimental employee was in two stages: Before the implant (DCA, with5 treatments) and after the implant (DCA with factorial arrangement 5 x 3, with 15 treatments). The obtained results demonstrated that the best effects in the growth of grafts and implants of cocoa went when using of manure of bovine livestock and coffe pulp, since they expressed a bigger plant height (49,02 and 49,27cm), shaft diameter (8,38 and 8,01mm), number of leaves (16,2 and 16,67) and area foliar (0,25 and 0,33 m2); allowing to obtain grafts in smaller time, in comparison with agricultural earththat had bigger number of days to the injertación (220 days) and obtaining bigger profitability with coffee pulp and manure of of bovine implanted with IMC 67 (relationship beneficio/costo of 2,51). In the stage after the implant; bud size, number, long and wide of leaves it was influenced by the sources of organic matter, standing out manure of bovine, worm humus and coffee pulp; the prendimiento percentage, bud size was influenced by the clones; days to the brotamiento, diameter of the bud and days to thtransplant they were influenced by the interaction of the sources of organic matter and the clones in study.